(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
Wheat grown in Uzbekistan in a dry and hot climate has its own individual qualitative characteristics, differs in physic-chemical composition, technological properties from imported. When developing technological methods of grain processing in recent years, the use of a high-performance complex of new generation equipment with a high technological effect is taken into account. In particular, properly carried out hydrothermal treatment of grain mass directly affects the physic-chemical properties of grain. The main task of hydrothermal processing (GTO) of grain is to change its technological properties in the direction of their optimization and subsequent stabilization at this level. Therefore, this process is one of the main methods of controlling the technological properties of grain.